PRIMARY SPLIT THICKNESS SKIN GRAFTING FOR HAND AND FINGER DEFECTS: DO NOT HESITATE - Matic, Sladjana; Gambiroza, Katarina; Vukman, Petar; Milovanovic, Darko; Palibrk, Tomislav; Ille, Mihailo (Medical Research, 2023)
ABSTRACTINTRODUCTION Hand injuries often result in soft tissue defects. The treatment of these defects represents one of the most difficult challenges in reconstructive surgery. There are numerous options for covering soft tissue defects, including flaps and skin grafts. MATERIAL AND METHODS This is retrospective observational study which includes seventeen patients with 24 skin defects of the hand who were treated by primary STSG in a single center. The average follow-up period was 6 months. The age of the patients ranged from 36 to 80 years. The majority of patients (16) were males, and one patient was female. Skin defects varied in size from 7x8mm to 39x40mm. Primary measures were STSG survival, recipient site infection and donor site morbidity. Secondary measures were cosmetic appearance and time needed for complete wound healing.RESULTS All 24 wounds healed successfully in a mean of 28,11±9,94 days. Graft infections haven't occurred. Partial graft loss occurred in one case. There was no major donor site morbidity reported. Six patients described the cosmetic result as good (score 3), 10 patients as acceptable (score 2) and one patient as poor (score 1).CONCLUSION Split thickness skin graft is an excellent option for immediate treatment of hand and finger skin defects. This method is simple, has less consequences than secondary grafts, requires minimum equipment and can sometimes be done in the emergency room, without the need to hospitalize the patient. Therefore, there is no need to be afraid of primary skin grafting. Keywords: hand, finger, soft tissue defects, primary reconstruction, split-thickness skin graft
Keywords: hand; finger; soft tissue defect; primary reconstruction; split-thickness skin graft